Love, Sex, and Exchange in the Context of Peacebuilding in the Democratic Republic of Congo. Issue 4 (8th August 2022) - Gibson, Kaitlin; Dixon, Alina; Goebel, Allison; Bartels, Susan
ABSTRACT: The narrow framing of Sexual Exploitation and Abuse (SEA) and the United Nations Zero-Tolerance Policy inadequately accounts for the range of sexual interactions in peacekeeping contexts and obscures the wider social contexts within which sexual decision making occurs. We draw on personal narratives from women who have had such sexual interactions, as well as community observers to demonstrate the complexity, multiple forms and ambiguities that characterize these relationships. We focus particularly on 'love' and long-term relationships. The complexities revealed cast doubt on the efficacy and appropriateness of the UN's zero-tolerance policy and call for a modification of the concept of the peacekeeping economy to include consideration of intimacy, emotion and quests to fulfil expectations of gendered social roles in the contradictory landscape of peacekeeping.